A prospective observational study to describe magnetic resonance imaging findings in perinatal asphyxia in terms of severity, outcome and neurological sequel in term and preterm babies - Mondal, Tanushree; Gayen, Gargi; Bhowmik, Arijit (International Journal of Contemporary Pediatrics, 2020)
Background: Perinatal asphyxia is a significant cause of neonatal mortality and morbidity. MRI is useful for assessing the severity and pattern of brain injuries. There is less data of MRI findings of perinatal asphyxia from India and the subcontinents. This prospective observational study was done to describe MRI brain findings in neonates with perinatal asphyxia with respect to various determinants. Methods: Initial MRI brain was done when babies were stable after fulfilling inclusion criteria. Immediate outcome was assessed at the end of hospital stay. They were followed up for presence of any sequel up to 1 year. Repeat MRI brain was done in few selected babies. Data was collected and statistically analyzed. Results: Total 55 babies were included in the study (term 27, preterm 28). There were 9 babies in stage 1, 17 babies in stage II and 22 babies in stage III. MRI brain findings were normal in 8 and abnormal in 47 patients. There were Deep gray matter injury (DG) in 22, Para Sagittal subcortical white matter injury (PS) in 6, Germinal matrix haemorrage (GMH), intraventricular haemorrage (IVH) and Periventricular leucomalacia (PVL) in 12 and Mixed pattern of injury in 7 babies. Findings among 9 expired babies were: 4 (44.4%) DG, 2 (22.2%) GMH+IVH and 3 (33.3%) mixed. There was neurological sequel in 13 babies (48.1%). Babies with normal MRI initially had no sequel. Conclusion: Brain injury due to perinatal asphyxia follows several patterns according to gestational age and severity. Early and accurate recognition of these patterns with the help of MRI brain helps in managing the baby and predicting the prognosis.